Modeling the Impact of Mobile Financial Services on Financial Literacy in Rural Bangladesh: A UTAUT2-Based Approach - Noor, Md Asad (South Asian Journal of Social Sciences and Humanities, 2025)
This paper examines how mobile financial services (MFS) shape financial literacy in rural Bangladesh through the UTAUT2 lens. We surveyed 432 rural MFS users across five districts and analyzed the data with SmartPLS 4.0 using structural equation modeling. The measurement model met standard criteria for reliability and convergent/discriminant validity. In the structural model, performance expectancy, effort expectancy, social influence, hedonic motivation, and price value emerged as the strongest drivers of behavioral intention to use MFS. Facilitating conditions and habit were positively related to actual use, and behavioral intention strongly translated into usage. Crucially, MFS use showed a positive and statistically significant association with financial literacy, suggesting that routine engagement with mobile money enhances users’ financial knowledge, awareness, and decision-making. The findings point to practical steps for policymakers and providers: improve usability and infrastructure in rural areas and run community-based awareness campaigns to broaden adoption. Pairing in-app literacy features or programs with MFS platforms could further accelerate financial empowerment outside urban centers. Conceptually, the study extends UTAUT2 by linking adoption determinants and subsequent usage to downstream financial-literacy outcomes, offering new insight into the socioeconomic effects of digital financial inclusion in rural settings.